Enrolling Migrant Children in Formal Education System: A Case Study of Major Issues in Varanasi City - Nahak, Prasanta Kumar (Voices of Teachers and Teacher Educators, 2019)
Children accompanying migrant parents are an educationally vulnerable group as they have limited access to formal system of education. They belong to a category for whom appropriate policies and adequate strategies are not in place. In spite of nation-wide implementation of Right to Education (RTE) Act, government has not completely mapped the distress of these migrant children who face problems in accessing educational opportunities. This paper uncovers the difficulties and obstacles in the enrolment of these children into the formal system of education. In doing so, this study examines the lacunae in the current education system which accommodates migrant children with difficulty and lacks a progressive attitude in the implementation of measures for the educational rights of migrant children. Qualitative research methods of observation and interview were used to obtain data. The results show that although migrant children are allowed in public schools, no specific policy to persuade migrant parents to bring their children to school exist, resulting in poor access to formal education for these children.